2008
DOI: 10.1007/s11270-008-9879-5
|View full text |Cite
|
Sign up to set email alerts
|

Sediment–Water Interactions of Bisphenol A Under Simulated Marine Conditions

Abstract: The sorption behavior of bisphenol A (BPA) on marine sediments treated using different methods was investigated in batch equilibrium experiments. Adsorption isotherms were well fitted to Freundlich model and the model parameters, K F and n, had been evaluated. When temperature decreased from 308 to 288 K, Freundlich constant (K F ) increased about 200%. K F increased by approximately 92.6% with increase of salinity from 1:2 artificial seawater (1:2 ASW) to ASW conditions. The plateau sorption capacity was arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…In the abovementioned experiment, BPA interacted the least with humic acids. This interaction was indicated in the study by Tian et al (2009) by a dramatic decrease in pH above 8.34 when BPA transferred to its anionic form and became more negatively charged. Samples from the near-bottom water layer (Staniszewska et al, 2015) were characterized by pH in the range 7.0-8.6, and only three samples had a pH value above 8.34.…”
Section: The Pollution Of Sediments In the Gulf Of Gdansk By Bpamentioning
confidence: 72%
See 2 more Smart Citations
“…In the abovementioned experiment, BPA interacted the least with humic acids. This interaction was indicated in the study by Tian et al (2009) by a dramatic decrease in pH above 8.34 when BPA transferred to its anionic form and became more negatively charged. Samples from the near-bottom water layer (Staniszewska et al, 2015) were characterized by pH in the range 7.0-8.6, and only three samples had a pH value above 8.34.…”
Section: The Pollution Of Sediments In the Gulf Of Gdansk By Bpamentioning
confidence: 72%
“…It has been observed in several studies that BC plays a decisive role in the sorption of PAHs in sediments that are high in black carbon and low in organic carbon (Staniszewska et al, 2011). In sediments that are high in organic carbon, the predominant phenomenon may be that of organic matter competing against BPA for hole-filling in elemental carbon, which as a result weakens the sorptive abilities of BC in relation to BPA (Tian et al, 2009). Zeng et al (2006) reported a higher sorptive capacity (about 30%) in relation to BPA in sediments thermally deprived (at 375°C) of organic matter.…”
Section: The Pollution Of Sediments In the Gulf Of Gdansk By Bpamentioning
confidence: 99%
See 1 more Smart Citation
“…The black carbon, compared with other components in the OC, was relatively refractory and was not easily oxidized by oxidant [20]. In addition, Yang and Zhang [19] and Tian et al [22] used the same method to treat the sediment samples and measured the OC before and after H 2 O 2 treatment. Their results showed that approximately 83% and 81% of the original OC was removed, respectively [19,22].…”
Section: Sediment Collection and Treatmentmentioning
confidence: 99%
“…In addition, Yang and Zhang [19] and Tian et al [22] used the same method to treat the sediment samples and measured the OC before and after H 2 O 2 treatment. Their results showed that approximately 83% and 81% of the original OC was removed, respectively [19,22]. This evidence confirms that most OC can be oxidized by this treatment, but the most refractory part of OC (e.g., the black carbon) remains in the marine sediments.…”
Section: Sediment Collection and Treatmentmentioning
confidence: 99%